2019
DOI: 10.1038/s41598-019-39388-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-acidic fusion minipeptides escort the intrinsic antioxidative ability of the pattern recognition receptor CRP in non-animal organisms

Abstract: C-reactive protein (CRP) is widely used as a biomarker of inflammation. It plays important roles in innate immunity response as a member of pattern recognition receptors, by binding oxidation-specific epitopes including some intermediates of lipid oxidative chain reaction. The inferred antioxidative ability of CRP was ever demonstrated by only few in vitro evidences, and needs to be clarified especially in vivo . Herein, we expressed human CRP in three representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…The interactions disrupted hydrogen bonds and converted the original helical structure into other structures. The decrease in the α‐helix content also suggested that AHTN changed the HLF backbone 50 . AHTN interacts with the amino acids in the HLF protein chain and changes the secondary HLF structure.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The interactions disrupted hydrogen bonds and converted the original helical structure into other structures. The decrease in the α‐helix content also suggested that AHTN changed the HLF backbone 50 . AHTN interacts with the amino acids in the HLF protein chain and changes the secondary HLF structure.…”
Section: Resultsmentioning
confidence: 97%
“…The decrease in the α-helix content also suggested that AHTN changed the HLF backbone. 50 AHTN interacts with the amino acids in the HLF protein chain and changes the secondary HLF structure.…”
Section: Spectroscopymentioning
confidence: 99%
“…Chlorophyll a (Chla), chlorophyll b (Chlb) and total chlorophyll (Chlt) were determined using Arnon's (1949) equations. Lipid peroxidation was determined by using the TBA (thiobarbituric acid) reaction, and then the MDA content was quantified [50,51].…”
Section: Chlorophyll Pigment and Mda (Malondialdehyde) Determinationmentioning
confidence: 99%
“…For the problem of determining the characteristics to be analyzed, a set of diagnostic images of tobacco membranes was processed to reveal the oxidation chain, resulting in the study of lipids as input samples to the anti-oxidation model [13]. On the other hand, the patterns or characteristics that are considered as inputs were calculated with the combination, weighting, and grouping of samples of electrical energy consumption to predict the dynamics of transmission management [14].…”
Section: Patternsmentioning
confidence: 99%